2016
DOI: 10.3758/s13420-016-0248-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of effort and difficulty on human preference for a stimulus: Investigation of the within-trial contrast

Abstract: The within-trial contrast hypothesis (WTC) provides a more parsimonious explanation for the phenomenon that humans and animals prefer outcomes that follow more effortful events to outcomes that follow less effortful events (Zentall, 2013). We conducted two WTC experiments with human adults. In Experiment 1, we manipulated the difficulty of a preceding event by varying the interresponse time and the limited-hold interval during differential reinforcement with a low response rate schedule, to examine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Pigeons responded more to an alternative after a high investment (i.e., higher rate of pecking) than a low investment (i.e., lower rate of pecking). Similar results have been obtained with humans (e.g., Tsukamoto, Kohara & Takeuchi, ). These findings predict that the reinforcement value of the standard alternative should be higher in the HR than the LR phases.…”
Section: Discussionsupporting
confidence: 88%
“…Pigeons responded more to an alternative after a high investment (i.e., higher rate of pecking) than a low investment (i.e., lower rate of pecking). Similar results have been obtained with humans (e.g., Tsukamoto, Kohara & Takeuchi, ). These findings predict that the reinforcement value of the standard alternative should be higher in the HR than the LR phases.…”
Section: Discussionsupporting
confidence: 88%
“…The within-contrast effort effect has been replicated in starlings (Kacelnik & Marsh, 2002) and humans (Klein, Bhatt, & Zentall, 2005; Tsukamoto & Kohara, 2017; Tsukamoto, Kohara, & Takeuchi, 2017) using comparable tasks. Conceptually, the within-trial contrast effect has also been demonstrated when the contrast involved a stimulus signaling a transition from a long delay (e.g., Digian, Friedrich, & Zentall, 2004) or a transition to food when the organism was in a relatively more extreme food deprived state (e.g., Marsh, Schuck-Paim, & Kacelnik, 2004).…”
Section: Effort and Self-controlmentioning
confidence: 87%
“…In contrast, when an action is evaluated retrospectively, effort tends to inflate the value of a realised reward (Alessandri et al, 2008, Wang et al, 2017, Aronson and Mills, 1959. For example, animals tend to prefer outcomes that have previously been associated with more effortful behaviour (Singer et al, 2007, Tsukamoto et al, 2017, Klein et al, 2005. Returning to our earlier example, these frameworks predict that the views atop the mountain would be more rewarding if we chose to climb to the peak rather than take the chairlift.…”
Section: Introductionmentioning
confidence: 86%